INVESTIGATION OF BIOPLASTICS IN TERMS OF SUSTAINABLE DESIGN APPROACH - (:unkn) unknown (ANADOLU UNIV, 2021)
The choice of material is one of the most important issues in terms of sustainable design approach regardless of the field of design. The protection of renewable resources, fossil-based fuel usage during production, their effects on humans and other organisms in nature, recycling capacity, the chemicals that emerge during waste disposal, in short, the environmental impact is out most importance in selection of materials. Plastics are used so widely that we can call the age we live in as the plastic age however plastics continue to be a growing problem for the environment. The use of bioplastics developed as an alternative to their petroleum-based counterparts has become widespread, with the expectation of solving problems caused by conventional plastics. The raw materials used to produce some bioplastics are also sources of food for human consumption. Therefore, a comprehensive study is much needed in terms of life cycle assessment. In addition to economic costs, both threats to food safety and some nature of chemicals used in agricultural production are factors that can change the balance. Whether bioplastics are completely environmentally friendly alternatives to petroleum-based plastics is a debatable issue. Although research reveal certain advantages to using bioplastics, in real life so far the effect on the environment has not proved to be as positive as expected. A literature review analyzing both the possitive and the negative aspects of the bioplastics is conducted so that a more objective perspective can be achieved in accordance with sustainable design principles.
Keywords: Bioplastics; Biodegradable Plastics; Sustainable Design; Life cycle Assessment; PERCEPTION